2015
DOI: 10.1021/acsnano.5b03075
|View full text |Cite
|
Sign up to set email alerts
|

Self-Biased Hybrid Piezoelectric-Photoelectrochemical Cell with Photocatalytic Functionalities

Abstract: Utilizing solar energy for environmental and energy remediations based on photocatalytic hydrogen (H2) generation and water cleaning poses great challenges due to inadequate visible-light power conversion, high recombination rate, and intermittent availability of solar energy. Here, we report an energy-harvesting technology that utilizes multiple energy sources for development of sustainable operation of dual photocatalytic reactions. The fabricated hybrid cell combines energy harvesting from light and vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 54 publications
(70 reference statements)
0
61
0
Order By: Relevance
“…The ever-increasing demand of energy as well as the deterioration of global climate and environment has spurred continuous research efforts to explore novel eco-friendly technologies, such as photocatalysis, [1][2][3][4][5][6][7][8][9][10][11][12][13] electrocatalysis, [2,[14][15][16][17][18][19][20][21][22] supercapacitors, [14,[23][24][25][26][27][28][29] and batteries, [30][31][32][33][34][35][36][37] for the utilization of green and renewable energy resources. Electrochemical water splitting, these noble-metal-based catalysts are economically not viable for wide-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…The ever-increasing demand of energy as well as the deterioration of global climate and environment has spurred continuous research efforts to explore novel eco-friendly technologies, such as photocatalysis, [1][2][3][4][5][6][7][8][9][10][11][12][13] electrocatalysis, [2,[14][15][16][17][18][19][20][21][22] supercapacitors, [14,[23][24][25][26][27][28][29] and batteries, [30][31][32][33][34][35][36][37] for the utilization of green and renewable energy resources. Electrochemical water splitting, these noble-metal-based catalysts are economically not viable for wide-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…Ag NWs were prepared by a modified polyrol process, reported in the literature . Specifically, 1.2 g of FeCl 3 solution (0.5 mM in ethylene glycol—EG), 0.135 g of AgNO 3 , and 0.05 g of polyvinylpyrrolidone (PVP) were added to 15 mL of EG and fully mixed.…”
Section: Methodsmentioning
confidence: 99%
“…Ag NWs were prepared by a modified polyrol process, reported in the literature. 19 Specifically, 1.2 g of FeCl 3 solution (0.5 mM in ethylene glycol-EG), 0.135 g of AgNO 3 , and 0.05 g of polyvinylpyrrolidone (PVP) were added to 15 mL of EG and fully mixed. Then the mixture was heated F I G U R E 5 LSV curves of light A, wavelength (red and blue denote red and blue light, respectively, and the power outputs for both red and blue light is 0.2 W) and (B-D) intensity effect (delivered by various power output) on HER current densities: B, ANS-1, C, ANS-2, and D, ANS-3.…”
Section: Synthesis Of Ag Nws@siomentioning
confidence: 99%
“…[35] As at ypical piezoelectric material, ZnO is employed to capture mechanical energy and provides ap iezoelectric polarization field in heterojunctions.In2016, Wang et al revealed the potential of piezotronics in photocatalysis on account of the research of polarization-induced interface band bending by assembling TiO 2 nanoparticles onto ZnO nanoplatelets. [36] Meanwhile,Hong et al reported the preparation of CuS/ZnO heterostructured nanowire arrays by vertically aligning them on stainless steel mesh using as imple two-step wet-chemical method (Figure 7a,b) [37] TheC uS/ ZnO nanocomposite displayed excellent piezo-photocatalytic performance for degrading MB (degradation ratio of % 100 %w ithin 20 min) under light and ultrasonic irradiation (Figure 7c), and is ascribed to the interfacial polarization field caused by ZnO nanowires.D riven by this polarization field, the photoinduced e À in the conduction band (CB) of CuS moved to that of ZnO,w hile the h + migrated from the valence band (VB) of ZnO to that of CuS.A s aconsequence,the photogenerated e À /h + pairs were separated at the interface of the CuS/ZnO nanowires,benefitting photocatalysis.A similar strategy is also applied in Ag/Ag 2 S-ZnO/ZnS branched heterostructures [38] and TiO 2 /ZnO nanowires, [39] and all depend on ZnO to provide apiezoelectric polarization field for promoting interface charge separation.…”
Section: Piezoelectric Polarization Promoted Surface Charge Separationmentioning
confidence: 99%
“…Comparison of photocatalytic performance over catalysts based on polarization-promoted surface charge separation.CuS/ZnO UV-vis light + ultrasonic Degradation of MB (c = 5mgL À1 ) K obs = 0.82 min À1 [37]Vulcanized ZnO-Ag/Cu UV light + ultrasonic Degradation of MB (c = 10 ppm) K obs = 0.015 min À1[38] TiO 2 /ZnO nanowires UV-vis light + ultrasonic Degradation of 4-NP (c = 5mgL À1 )/ 2,4-DCP (c = 5mgL À1 ) K obs = 1.19 h À1 K obs = 1.11 h À1…”
mentioning
confidence: 99%